Innovation processs in Agro food distribution - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Distribution of food products includes all activities which ensure the passage of these categories of goods, from traders producers, to end consumers or users. On this regard, it will be presented the following: distribution channel and its dimensions, innovation strategy of industrial distribution channel. Also, it can be shaped a number of recommendations for improving innovation process in agrofood distribution.
Keywords: 330; distribution channel; agrofooddistribution; innovation process